Odpowiedzi

2010-03-29T15:15:23+02:00
A)
a=k(x+y)
k= a/(x+y)
f)
(k+a)*f=k+1
kf+af=k+1
kf-k=1-af
k(f-1)=1-af
k=(1-af)/(f-1)
g)
1/k=2-g
1=(2-g)*k
k=1/(2-g)
h) k²+k-h=0
Δ = 1+4h
k1=(-1-√(1+4h))/2
k2=(-1+√(1+4h))/2
i)
2/k=i-a/2
2=ik-ak/2
2=k(i-a/2)
k=2/(i-a/2)
wydaje mi się że jest dobrze :)
5 3 5
Najlepsza Odpowiedź!
2010-03-29T15:30:36+02:00
A)
a= xk+yk
xk+yk=a
k(x+y)=a /:(x+y)
k=a/x+y

f)
f= k+1/k+a /*k
kf=k+1+ak
kf-k-ak=1
k(f-1-a)=1/:(f-1-a)
k=1/f-1-a

g)
g= 2-1/k /*k
kg=2k-1
kg-2k=-1
k(g-2)=-1/:(g-2)
k=-1/g-2

h)
h=ka2+k
ka2+k=h
k(a2+1)=h/:(a2+1)
k=h/a2+1
Robiliśmy to na lekcji i powinno być dobrze :)
5 5 5